Treatment of cosmetic industry wastewater with boron doped diamond, platinum and metal oxide electrodes in electrooxidation process - Can, Orhan Taner; Gundogdu, Hilal; Keyikoglu, Ramazan; Elibol, Pinar Sevim; Aygun, Ahmet; Isleyen, Mehmet (Pamukkale Univ, 2024)
In this study, treatability of cosmetic wastewater consist high pollution by electrooxidation process was investigated using three different anodes. For this purpose, BDD (Boron Doped Diamond), Pt and RuO2- IrO2 metal -oxide electrodes were used. The total organic carbon (TOC) removal efficiency of each electrode was determined and results were compared. After 120 min of operating time, the TOC removal efficiencies of BDD anode were obtained as 31.6%, 57.8% and 68%; Pt anode were obtained as 25%, 36.5% and 48%; RuO2-IrO2 metal -oxide anode were obtained as 22.6%, 29.8% and 42.6% respectively for 0.5, 1 and 1.5 ampere currents. It is observed that TOC removal efficiency increases with time for all electrodes throughout the operation time. The results showed that BDD electrode provided the best removal efficiency and this efficiency increased by the time of progress. After 120 min of operating time, the best TOC removal efficiencies of BDD, Pt and RuO2-IrO2 metaloxides electrodes were 68%, 48% and 42.6% respectively for 1.5 ampere.
Keywords: Cosmetic industry wastewater; Advance oxidation process; Electrooxidation; BDD electrode